1976
DOI: 10.1021/ic50157a005
|View full text |Cite
|
Sign up to set email alerts
|

Anionic linear chain iridium carbonyl halides

Abstract: The compounds Ko.60Ir(CO)2Ch-0.5H20, (TTF)o.6iIr(CO)2Ch (TTF = tetrathiafulvalenium), Ko.57lr(CO)2Bn-0.2C-H3COCH3, and Cso.6oIr(CO)2Br2 have been investigated by chemical analysis, infrared and 193Ir Mossbauer spectroscopy, electrical conductivity, and magnetic susceptibility measurements. Conducting linear chains of cw-[Ir(CO)2X2]°60-(X = Cl, Br) units are shown to be present in these compounds. The apparently well-defined compounds Ko.98lr(CO)2-CI2.42O.2CH3COCH3 and Nao.93lr(CO)2Cl2.32-0.3CH3COCH3 are reform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…IR measurements can give information about the relative disposition of the chloro ligands in organometallic [Ir]Cl 2 fragments. Thus, for a cis disposition two IR-active ν(IrCl) frequencies are expected in the region 400−200 cm -1 , while a trans disposition would display only one characteristic band . IR spectra of 14A and the 3:4:2 mixture of 14A : 14B : 14C were recorded in the range 700−200 cm -1 (solid state, CsI pellets).…”
Section: Resultsmentioning
confidence: 99%
“…IR measurements can give information about the relative disposition of the chloro ligands in organometallic [Ir]Cl 2 fragments. Thus, for a cis disposition two IR-active ν(IrCl) frequencies are expected in the region 400−200 cm -1 , while a trans disposition would display only one characteristic band . IR spectra of 14A and the 3:4:2 mixture of 14A : 14B : 14C were recorded in the range 700−200 cm -1 (solid state, CsI pellets).…”
Section: Resultsmentioning
confidence: 99%
“…Older compounds in this series include A 0.60 Ir(CO) 2 X 2 , with A = K, Cs, TTF (TTF = tetrathiafulvalene). [ 15 ] Newer ones arise from electrochemically oxidized [Ir(CO) 2 X 2 ] -, X = Cl, Br, I. [16,17] And there is the beautiful series of partially supported oxidized Ir chains from the Oro and Ciriano groups, [18,19,20,21,22] one example of which is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the known partial oxidation process involving the metal centres in the Ru 0 -Ru 0 chain [6,14], the short Ru-Ru bond length and the proposed structure [16] makes the material similar to well conducting, partially oxidised chains formed by stacking of e.g. square-planar Pt [17] or Ir [18] d 8 complexes. We have also recently found that the film conductance increases following partial oxidation [19].…”
Section: Introductionmentioning
confidence: 99%